MANAJEMEN STRATEGI DALAM MENINGKATKAN MUTU PENDIDIKAN DHAMMASEKHA SADDHAPALA JAYA KABUPATEN TEMANGGUNG - Metta Puspita Dewi (STABN RADEN WIJAYA WONOGIRI, 2020)
Dhammasekha strategy management begins with 1) strategy of formulation which is identify the power been found in teacher professionalism, capabillity in the arts and culture, facilities and infrastructure, positive image. Weaknesses of Dhammasekha include funding sources, There is no patent curriculum, location are not strategic, doesn’t have an operational permit and the motivation of human resource still weak. Dhammasekha has the opportunity to be preferred educational institute for Buddhists because support of 16 Buddhists temple but has the threat of competition with others as a educational institution which is more active and creative close by Dhammasekha location. 2) Strategic of implementation has been done by creating programs or policies, forming organization structure according with competencies and motivating 3) evaluate strategic has been done regullary by the chairman to measure Dhammasekha performance and take an corrective action through involve by stakeholder teachers,leaders and representative of students to support the improvement quality of the institution. Dhammasekha focused on member of buddhism to get theirs satisfication , build up commitment, and continous teamwork improvement.